Feasibility of Using Autonomous Ankle Exoskeletons to Augment Community Walking in Cerebral Palsy - Collin D. Bowersock; Zachary F. Lerner (IEEE Open Journal of Engineering in Medicine and Biology)
Objective: This pilot study investigated the feasibility and efficacy of using autonomous ankle exoskeletons in community settings among individuals with cerebral palsy (CP). Five participants completed two structured community walking protocols: a week-long ankle exoskeleton acclimation and training intervention, and a dose-matched Sham intervention of unassisted walking. Results: Results demonstrated significant improvements in acclimatized walking performance with the ankle exoskeleton, including increased speed and stride length. Participants also reported increased enjoyment and perceived benefits of using the exoskeleton. While ankle exoskeleton training did not lead to significant improvements in unassisted walking, this study demonstrates the feasibility of using ankle exoskeletons in the real world by people with CP. Conclusions: This study highlights the potential of wearable exoskeletons to augment community walking performance in CP, laying a foundation for further exploration in real-world environments.